IDENTIFIKASI MISKONSEPSI SISWA MENGGUNAKAN FOUR-TIER DIAGNOSTIC TEST PADA MATERI OPTIK GEOMETRI - Widya Bratha Sheftyawan; Trapsilo Prihandono; Albertus Djoko Lesmono (FKIP Universitas Jember, 2018)
ABSTRACT The purpose of this study was to describe the misconception that students on the geometricoptics use a Four-Tier Diagnostic Test in SMAN 1 Cluring. The population in thisresearch is the entire class XI in SMAN 1 Cluring. The selected samples for research area class of XI MIPA2, XI MIPA 3, and XI MIPA 4 which is selected using the method ofpurposive sampling area. Data collection methods used in this research is a method ofdocumentation and tests. The instruments used multiple choice diagnostic test shaped fourlevel. Based on the results of data analysis and discussion can be known that overallmisconception that students on the subject of geometric optics in SMAN 1 Cluring of37.62% so this qualifies a misconception to medium levels.Keywords: Misconception, Four-Tier Diagnostic Test, Geometric Optics